Linguistic Chameleon: Syntactic Functions of “Kuan” (Cebuano language filler) in Social Media Conversations - Rose Carmel Tabotabo; April Joy Delina; Kim Rotante; Shendy Rabago; Sophia Marie Diel; Ruel T. Bonganciso (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2024)
The study explored the syntactic functions of “kuan” in social media conversations and in the logs, reels, and shorts of various Cebuano content creators. Taking into account related studies on fillers, the researchers discovered that there is still no known study of its syntactic functions. Hence, the researchers will analyze the syntactic functions of filler words, specifically the Cebuano filler “kuan” used by content creators. Understanding the syntactic functions of these words contributes to the body of language research by offering some insights into people’s communication patterns on social media. This contributes to our understanding of the versatility of “kuan” within the context of social media use. The researchers will be using content analysis to examine how Cebuano content creators used ”kuan” in their logs, shorts or reels and analyze their syntactic functions. The researchers have concluded that